2019
DOI: 10.1177/1470785319858598
|View full text |Cite
|
Sign up to set email alerts
|

Let’s put a smile on that scale: Findings from three web survey experiments

Abstract: Graphical symbols such as smileys and other emoticons are prevalent in everyday life. Paralleling their increasing use in private text messaging and even in business communication, smileys and other emoticons also have been used more frequently in surveys. So far, only a few studies have tested the effects of smiley faces as rating scale labels on the response process in web surveys. This study compared smiley face scales with verbally labeled rating scales in three web survey experiments. We found no convinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Possible solutions might include color coding or other visual design features of questions that give meaning to scale points (e.g., "green" for positive or "red" for negative, "thumps up" for agreement and "thumps down" for disagreement) and provide clues on how scale points relate to each other (e.g., by tuning down color by 50%). Research in this area is budding (Stange et al, 2018;Toepoel & Dillman, 2010;Toepoel & Funke, 2018;Toepoel et al, 2019;Tourangeau et al, 2007), although recent studies on the use of smiley faces were not encouraging in terms of data quality and ease of cognitive response processing (Cernat & Liu, 2019;Gummer et al, 2020). Unless convincing progress is made to make rating scales more compact and less screen size space consuming, for now, we recommend complying with the classical advice on using fully labeled rating scales with verbal labels (e.g., Krosnick & Fabrigar, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Possible solutions might include color coding or other visual design features of questions that give meaning to scale points (e.g., "green" for positive or "red" for negative, "thumps up" for agreement and "thumps down" for disagreement) and provide clues on how scale points relate to each other (e.g., by tuning down color by 50%). Research in this area is budding (Stange et al, 2018;Toepoel & Dillman, 2010;Toepoel & Funke, 2018;Toepoel et al, 2019;Tourangeau et al, 2007), although recent studies on the use of smiley faces were not encouraging in terms of data quality and ease of cognitive response processing (Cernat & Liu, 2019;Gummer et al, 2020). Unless convincing progress is made to make rating scales more compact and less screen size space consuming, for now, we recommend complying with the classical advice on using fully labeled rating scales with verbal labels (e.g., Krosnick & Fabrigar, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A LSS apresenta 40 questões para cada versão e o instrumento é composto por uma escala de Likert de 5 frações (1=Nunca; 5= Sempre). Pela especificidade da população, recorreu-se a uma smiley face scales pelo facto de ser um sistema familiar para estes atletas (De Knegt, Schuengel, Lobbezoo, Visscher, Evenhuis, Boel, & Scherder, 2016) e constituir-se como uma plataforma de substituição dos rótulos numéricos (Gummer, Vogel, Kunz, & Roßmann, 2019).…”
Section: Instrumentosunclassified
“…Dillman et al (1998) found that respondents were more likely to complete a “plain” version of a survey as opposed to a “fancy” version embellished with colors and graphics, which they attributed to the increased burden of longer download times for respondents in the visually enhanced version. In a study testing the effects of smiley face emoticons as labels on rating scales in place of verbal labels, Gummer et al (2020) found no significant advantages in response quality among respondents shown rating scales with the emoticons; instead, their use increased response time. Similarly, studies have shown that slider scales, in which respondents move a “handle” or bar to indicate their response on a continuous scale, are more susceptible to measurement errors and generate longer response times, more break-offs, and higher item omissions than traditional rating scales (Funke, 2016; Roster et al, 2015).…”
Section: Introductionmentioning
confidence: 98%